Optimum Rower Weight Position for Competition Development - Khunopast, Jiraporn; Bunyawanichakul, Pracha; Senakham, Tanormsak; Hemhirun, Surachai (Srinakharinwirot University Engineering Journal, 2023)
The purpose of this research was to optimize rower weight position for Competition Development using Ansys Workbench. A rowing model was made to calculate results. There were three types of analysis, as follows: 1) rowers with a heavy weight were seated at the front of the boat; 2) rowers with a heavy weight were seated in the middle of the boat; and 3) rowers with a heavy weight were seated at the rear of the boat. The results obtained were compared to identify the positions of the weights of the rowers to ensure the boat reached maximum efficiency in racing. According to the study, the positions of the weights of the rowers that enabled the boat to reach maximum efficiency in racing was assigning rowers with a heavy weight to sit in the middle of the boat since the weight was distributed appropriately, and the resistance affected dragon boat movement was at the lowest, 339.156 Newton and the lift was at the highest, 9,268.35 Newton, the highest speed in rowing was 3.817 meter per second, and the least time spent on rowing was 53.00 seconds, compared to other types. Therefore, the arrangement of the positions of rowers is essential for dragon boat racing. The information obtained from the analysis can be applied to achieve the maximum benefit for dragon boating accordingly.